Pelaksanaan Perdamaian Dalam PKPU Koperasi Simpan Pinjam Indosurya Cipta Dengan Para Anggotanya Dihubungkan Undang-Undang No 37 Tahun 2004 - Nasikah Nasikah; Andhyka Muchtar; Rasman Habeahan (Desanta Publisher, 2024)
This research examined the implementation of peace in the postponement of debt payment obligations (PKPU) of Indosurya Cipta Savings and Loan Cooperative with its members in the context of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. The method used was a literature study by collecting and analyzing data from various literature sources such as books, journals, scientific articles, laws and regulations, and other related documents. The results showed that PKPU is a legal effort to prevent bankruptcy by providing an opportunity for debtors and creditors to negotiate a peace plan. During the PKPU period, the debtor cannot manage the company or its assets without court approval. A court-approved peace plan is binding on all creditors, except secured creditors who do not agree to it. In the case of Indosurya Cipta Savings and Loan Cooperative, legal steps that can be taken by cooperative members include administrative, civil, and criminal law enforcement means.